ROS functions as an upstream trigger for autophagy to drive hematopoietic stem cell differentiation. Issue 10 (25th November 2016) - Cao, Yan; Fang, Yixuan; Cai, Jinyang; Li, Xin; Xu, Fei; Yuan, Na; Zhang, Suping; Wang, Jianrong
Abstract : Background and objectives : We have recently described a mechanistic action of autophagy on hematopoiesis in which autophagy sustains hematopoietic stem cell multilineage differentiation by direct targeting of intracellular Notch. However, the upstream signal that triggers autophagy to degrade Notch during hematopoiesis remains elusive. Methods : Conditional autophagy-essential gene Atg 7 knockout mouse model is used for identifying signals regulating autophagy in the promotion of hematopoiesis. Results : We find here that generation of reactive oxygen species (ROS) is progressively increased during hematopoietic stem cell differentiation, and inhibition of ROS production was found to attenuate the differentiation of hematopoietic stem cells. In hematopoietic stem and progenitor cells (HSPCs) of wild-type mice, inhibition of ROS production downregulated autophagy activity but upregulated intracellular Notch and its downstream effectors. In contrast, in the HSPCs of autophagy fully defective mice, ROS inhibition did not alter myeloid differentiation, and hematopoietic stem cell differentiation to multi-lineages no longer responded to ROS inhibition. Discussion : The ROS-regulating hematopoiesis is mitochondrial origin, and this action depends on intact autophagy machinery capable of degrading intracellular Notch. Conclusion : ROS functions as an upstream signal in the autophagic promotion of hematopoietic stem cell differentiation.